2020
DOI: 10.7717/peerj.9963
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concurrent training on trainability performance factors in youth elite golf players

Abstract: Background Due to the early specialization of golf players, examining the within session sequence of training should be considered to enhance performance and prevent injury risk. The present study analyzed the effects of an 18-week concurrent training developed before or after a specific golf session in adolescence elite golfers on several performance factors. Methods Sixteen right-handed male golfers, were randomly divided into two groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 35 publications
2
14
1
1
Order By: Relevance
“…This hypothesis was confirmed by our results, since seven to ten trials were required to reliably measure swing performance in high-handicap players. These numbers of trials were higher than those recommended for low-handicap players (i.e., three to five trials) [ 5 , 6 , 7 , 8 , 10 , 20 ] and similar to those found for medium-handicap players (i.e., ten trials) [ 9 ]. Finally, Severin et al recommended between 4 and 12 trials for low-handicap players to measure kinematic and kinetic variables during swing performance [ 22 ].…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…This hypothesis was confirmed by our results, since seven to ten trials were required to reliably measure swing performance in high-handicap players. These numbers of trials were higher than those recommended for low-handicap players (i.e., three to five trials) [ 5 , 6 , 7 , 8 , 10 , 20 ] and similar to those found for medium-handicap players (i.e., ten trials) [ 9 ]. Finally, Severin et al recommended between 4 and 12 trials for low-handicap players to measure kinematic and kinetic variables during swing performance [ 22 ].…”
Section: Discussionsupporting
confidence: 52%
“…In this sense, Read et al found excellent reliability (i.e., ICC = 0.87) with low-handicap players when club head speed was measured with a driver using three trials [ 10 ]. Other studies using five trials also found excellent values for club head speed with low-handicap players (i.e., ICC > 0.9) [ 5 , 6 , 7 , 8 ]. Nevertheless, Weston et al found excellent reliability for club head speed (i.e., ICC = 0.84) with medium-handicap players (i.e., 11.2) but they had to perform ten trials [ 9 ].…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations